Modified energy based time-frequency features for classifying human emotions using EEG - M., Murugappan; R., Nagarajan; Sazali, Yaacob (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.